Perspektif Islam Tentang Pasar Uang dan Pengoperasian Pasar Uang Syariah - Sholahuddin, Muhammad Arif (Jurnal Ilmiah Ekonomi Islam, 2023)
The main focus of this research is the money market with Sharia standards, particularly short-term (interest-free) financial transactions done by means of cash market players or other cash market players. considering the fact that the acquisition of securities is brief term, buying and selling is carried out on the premise of agree with. The design of this studies is quantitative based totally on published journals related to the subject of this studies Islamic attitude on money Markets and Operations of Islamic money Markets. This observe makes use of a secondary facts library survey approach within the form of 20 journals published within the 2011-2021 length that have been posted in each countrywide and international medical journals to explore the Islamic cash marketplace attitude and money market Operations. The outcomes showed that based totally on a literature examine of 20 country wide and global posted journals based totally at the year the general public of journals had been published in 2016, there have been five journals (25%), the kind of descriptive studies was the majority of 15 journals (75%). , the majority of journal areas are from Indonesia, 12 journals (60%), and based totally on journal subjects, most of them are Islamic money marketplace and Interbank Islamic cash market with 6 journals every (30%).g Syariah Antar bank dengan masing-masing 6 jurnal (30%).